Epidermal architecture, growth, and metabolism in acromegaly. Issue 6008 (28th February 1976) - Holt, P J; Marks, R
Abstract : Epidermal architecture, replication, and anabolic activity were studied in six patients with acromegaly. Patients with acromegaly had significant larger viable epidermal cells than controls. The rates of incorporation of tritiated thymidine, proline, and histidine into skin slices in vitro was also significantly increased in acromegalic patients. The mean autoradiographic labelling indices after intracutaneous injection of triated thymidine were 8.4% in the acromegalic patients and 5.1% in the control group. None of the changes observed could be closely correlated with levels of serum growth hormone.